Uncertain Values An Axiomatic Approach to Axiological Uncertainty - Riedener, Stefan (Ideen & Argumente, 2021)
How should you evaluate your options if you're uncertain about what's fundamentally valuable? This book introduces an axiomatic approach to explicate and vindicate Expected Value Maximisation. The result is a formally cogent and philosophically compelling extension of standard decision theory and an original take on the problem of axiological or normative uncertainty.